EDUKASI DAN SENAM KESEHATAN REPRODUKSI PADA SISWA KELAS VI SD NEGERI 1 BANTERAN - Emilia, Silfi; Saputri, Meliana Loly; Tyas, Bekti Kusumaning; Cahyandari, Meita Dwi; Islamy, Nurul Izzah; Imaniar, Hervinda Yasfa; Fitri, Resty Desyani; Nadinnisa, Fadillah Puspa; Verari, Irena Anung; Kusumawardani, Lita Heni; Zaenudin, Arif (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2024)
School health nursing is one of the areas in community nursing that is focused on efforts to prevent and manage infectious diseases by emphasizing preventive and promotive efforts. Providing education related to reproductive health significantly affects individual sexual knowledge and behavior (Hu et al., 2023). Based on the results of the assessment that has been done at SD N 1 Banteran, the results show that from a total sample of 10 children, all of them do not understand what reproductive health is and how to maintain reproductive health and 3 out of 6 female students have menstruated. The purpose of this community service is that grade 6 students of SD Negeri 1 Banteran can understand about maintaining reproductive health. The target of this activity is 6th grade elementary school students consisting of 30 students. The target was determined based on the results of interviews and observations carried out using the observation sheet method through google forms. Activities were carried out with education and demonstrations in the school environment regarding reproductive health issues using the pretest and posttest methods. Based on the results of data analysis, it shows that there is a difference in the level of knowledge in the good category pretest as many as 10 students (33.3%) and posttest 19 students (63.35). Educational activities and reproductive health gymnastics have an effect on increasing students' knowledge related to reproductive health.